1988
DOI: 10.1007/bf00187364
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of two opposing, asymmetric curved wall jets

Abstract: An experimental investigation was made of a two dimensional flow formed by the interaction of two asymmetric turbulent curved wall jets past a circular cylinder. Measurements were made of velocity and turbulence intensity profiles of the two curved wall jets before the interaction, and those of the merged jet after the interaction. The location of the interaction region of the two opposing curved wall jets and the flow direction of the merged jet were found to depend primarily on the ratio of initial momentum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…It is seen that the approximate similarity has been already achieved at about 0 = 120 ~ Also contained in Fig. 3 are the velocity profiles of the plane wall jets (Irwin 1973;Kind and Suthanthiran 1973), and those of the curved wall jets (Rew and Park 1988;Wilson and Goldstein 1976). The velocity profiles of the present case are seen to be in good accord with the others.…”
Section: The Characteristics Of the Curved Wall Jet Before The Interasupporting
confidence: 78%
See 4 more Smart Citations
“…It is seen that the approximate similarity has been already achieved at about 0 = 120 ~ Also contained in Fig. 3 are the velocity profiles of the plane wall jets (Irwin 1973;Kind and Suthanthiran 1973), and those of the curved wall jets (Rew and Park 1988;Wilson and Goldstein 1976). The velocity profiles of the present case are seen to be in good accord with the others.…”
Section: The Characteristics Of the Curved Wall Jet Before The Interasupporting
confidence: 78%
“…An understanding of the physical process about the flow is important in the sense that it constitutes a typical problem of complex shear layer interaction and coalescence. Previous studies on the wall jet-waU jet interaction (Gilbert 1988;Kind and Suthanthiran 1973;Lee and Chung 1983;Rew and Park 1988) revealed that the velocity profiles of the merged jet were very similar to those of a conventional plane jet and that the merged jet spread more rapidly than the conventional one.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations